Change of Direction Biomechanics in a 180-Degree Pivot Turn and the Risk for Noncontact Knee Injuries in Youth Basketball and Floorball Players - Leppänen, Mari; Parkkari, Jari; Vasankari, Tommi; Äyrämö, Sami; Kulmala, Juha-Pekka; Krosshaug, Tron; Kannus, Pekka; Pasanen, Kati (The American journal of sports medicine, 2021)
Studies investigating biomechanical risk factors for knee injuries in sport-specific tasks are needed.BACKGROUNDStudies investigating biomechanical risk factors for knee injuries in sport-specific tasks are needed.To investigate the association between change of direction (COD) biomechanics in a 180-degree pivot turn and knee injury risk among youth team sport players.PURPOSETo investigate the association between change of direction (COD) biomechanics in a 180-degree pivot turn and knee injury risk among youth team sport players.Cohort study; Level of evidence, 2.STUDY DESIGNCohort study; Level of evidence, 2.A total of 258 female and male basketball and floorball players (age range, 12-21 years) participated in the baseline COD test and follow-up. Complete data were obtained from 489 player-legs. Injuries, practice, and game exposure were registered for 12 months. The COD test consisted of a quick ball pass before and after a high-speed 180-degree pivot turn on the force plates. The following variables were analyzed: peak vertical ground-reaction force (N/kg); peak trunk lateral flexion angle (degree); peak knee flexion angle (degree); peak knee valgus angle (degree); peak knee flexion moment (N·m/kg); peak knee abduction moment (N·m/kg); and peak knee internal and external rotation moments (N·m/kg). Legs were analyzed separately and the mean of 3 trials was used in the analysis. Main outcome measure was a new acute noncontact knee injury.METHODSA total of 258 female and male basketball and floorball players (age range, 12-21 years) participated in the baseline COD test and follow-up. Complete data were obtained from 489 player-legs. Injuries, practice, and game exposure were registered for 12 months. The COD test consisted of a quick ball pass before and after a high-speed 180-degree pivot turn on the force plates. The following variables were analyzed: peak vertical ground-reaction force (N/kg); peak trunk lateral flexion angle (degree); peak knee flexion angle (degree); peak knee valgus angle (degree); peak knee flexion moment (N·m/kg); peak knee abduction moment (N·m/kg); and peak knee internal and external rotation moments (N·m/kg). Legs were analyzed separately and the mean of 3 trials was used in the analysis. Main outcome measure was a new acute noncontact knee injury.A total of 18 new noncontact knee injuries were registered (0.3 injuries/1000 hours of exposure). Female players sustained 14 knee injuries and male players 4. A higher rate of knee injuries was observed in female players compared with male players (incidence rate ratio, 6.2; 95% CI, 2.1-21.7). Of all knee injuries, 8 were anterior cruciate ligament (ACL) injuries, all in female players. Female players displayed significantly larger peak knee valgus angles compared with male players (mean for female and male players, respectively: 13.9°± 9.4° and 2.0°± 8.5°). No significant associations between biomechanical variables and knee injury risk were found.RESULTSA total of 18 new noncontact knee injuries were registered (0.3 injuries/1000 hours of exposure). Female players sustained 14 knee injuries and male players 4. A higher rate of knee injuries was observed in female players compared with male players (incidence rate ratio, 6.2; 95% CI, 2.1-21.7). Of all knee injuries, 8 were anterior cruciate ligament (ACL) injuries, all in female players. Female players displayed significantly larger peak knee valgus angles compared with male players (mean for female and male players, respectively: 13.9°± 9.4° and 2.0°± 8.5°). No significant associations between biomechanical variables and knee injury risk were found.Female players were at increased risk of knee and ACL injury compared with male players. Female players performed the 180-degree pivot turn with significantly larger knee valgus compared with male players. However, none of the investigated variables was associated with knee injury risk in youth basketball and floorball players.CONCLUSIONFemale players were at increased risk of knee and ACL injury compared with male players. Female players performed the 180-degree pivot turn with significantly larger knee valgus compared with male players. However, none of the investigated variables was associated with knee injury risk in youth basketball and floorball players.